Stress distribution in lower second molar mesialization using mini-implants: a pilot study using 3D finite element analysis - da Silva, João Maurício Ferraz [UNESP]; Lisboa, Juliana da Costa [UNESP]; Pierre, Fernanda Zapater [UNESP]; de ARAÚJO, Rodrigo Máximo [UNESP]; Lemos, Cleidiel Aparecido Araujo; Cruz, Ronaldo Silva [UNESP]; Verri, Fellippo Ramos [UNESP] (Editora Cubo, 2023)
Objective: to analyze the stress distribution in a 3D model that simulates second molar mesialization using two different types of mini-implants. Material and Methods: a mandible bone model was obtained by recomposing a computed tomography performed by a software program. The cortical and trabecular bone, a lower second molar, periodontal ligament, orthodontic tube, resin cement and the mini-implants were designed and modeled using the Rhinoceros 4.0 software program. The characteristics of self-drilling orthodontic mini-implants were: one with 7 mm length, 1 mm transmucosal neck section and 1.6 mm diameter and another with 5 mm length and 1.5 mm diameter. A total of 235.161 and 224.505 elements were used for the mesh. These models were inserted into the bone block and then subjected to loads of 200 cN (centinewton). The results were calculated and analyzed by the Ansys 17.0 software program for qualitative verification through displacement and maximum principal stress maps. Results: it was possible to observe that the periodontal ligament presented low displacement and stress values. However, the physiological values presented are among those capable to provide orthodontic movement, with compression and tensile area visualization staggered between 0.1 and-0.1 MPa (megapascal). Conclusion: within the limitations of the study, the mini-implants tested showed similar results where the load on the tooth allowed dental displacement (molar mesialization), with a tendency to rotate it, theoretically allowing the second molar to take the location of the first molar.
Distribuição de tensões na mesialização do segundo molar inferior usando mini-implantes: um estudo piloto usando análise de elementos finitos 3D
Keywords: Finite element analysis; Fixed orthodontic appliances; Mini dental implants; Orthodontic anchorage procedures; Tooth dislocation